Peningkatan minat baca anak melalui program Reading fun for kids - Dina Rotua Sitanggang; Rogate Wahyuni Lumbantobing; Stefani Halgera Pakpahan; Endang Junita Sinaga (Universitas Maritim AMNI Semarang, 2024)
The majority of people living in Kelurahan Batang Beruh, Sidikalang Sub-district, Dairi Regency are school-age children between 6 and 12 years old. Children at this age are active learners. Therefore, innovation is needed in the organization of tutoring and reading terraces to increase insight, information and knowledge. Because with knowledge, children can at least begin to understand what they have ignored and considered unimportant, and turn it into something useful to improve their lives. The existence of reading fun for kids aims to stimulate children's interest in learning and reading, provide reading materials and places to study, provide satisfaction for parents for their children's love of learning and is a solution to increase motivation. improve and encourage learning and reading. The method used in this research is a qualitative method. This method keeps the data obtained from interviews and documents, but describes the activities more clearly and in detail. This activity aims to stimulate interest in learning and instill reading habits in children